2019
DOI: 10.1097/md.0000000000016379
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of computer-aided diagnosis system for the diagnosis of thyroid nodules on ultrasound

Abstract: Background: More and more automated efficient ultrasound image analysis techniques, such as ultrasound-based computer-aided diagnosis system (CAD), were developed to obtain accurate, reproducible, and more objective diagnosis results for thyroid nodules. So far, whether the diagnostic performance of existing CAD systems can reach the diagnostic level of experienced radiologists is still controversial. The aim of the meta-analysis was to evaluate the accuracy of CAD for thyroid nodules’ diagnosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Differentiation between benign and malignant TNs is challenging, even for experienced specialists. Accordingly, some recent studies have focused on S-Detect system efficacy in comparison to evaluations performed by experienced medical physicians or other types of evaluations using CAD [14,15]. A recent meta-analysis performed by Zhao et al including 723 lesions from five studies revealed that the sensitivity of the CAD was comparable to the assessment provided by experienced radiologists (0.87 vs. 0.88) but presented lower specificity (0.79 vs. 0.92).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differentiation between benign and malignant TNs is challenging, even for experienced specialists. Accordingly, some recent studies have focused on S-Detect system efficacy in comparison to evaluations performed by experienced medical physicians or other types of evaluations using CAD [14,15]. A recent meta-analysis performed by Zhao et al including 723 lesions from five studies revealed that the sensitivity of the CAD was comparable to the assessment provided by experienced radiologists (0.87 vs. 0.88) but presented lower specificity (0.79 vs. 0.92).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis performed by Zhao et al including 723 lesions from five studies revealed that the sensitivity of the CAD was comparable to the assessment provided by experienced radiologists (0.87 vs. 0.88) but presented lower specificity (0.79 vs. 0.92). However, there is a need for larger sample-size prospective studies to verify the clinical usefulness of CAD in a clinical setting, together with further technical improvements of the software [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing systematic reviews have been based on analyzing different textural techniques and machine learning algorithms and classifiers more on a biomedical engineering perspective rather than clinical applicability [13,17,18,19]. A recent systematic review and meta-analysis study focused on the diagnostic performance of mainly the Samsung S-Detect CAD software in comparison with that of radiologists for the differentiation of thyroid nodules in clinical settings [20]. As various CAD systems for ultrasound feature assessment of thyroid nodules have been developed by various researchers and clinicians in different parts of the world, there are multiple factors that can influence their diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%